Capacity worth of transmission-energy storage systems in renewable generation - Tan, Guang Wang. (2010)
Wind and solar power are attractive alternative as a power source because they are plentiful, renewable, widely distributed, clean, and produce no greenhouse gas emissions. As they are readily available, clean and free, there has been increasing interest in making use of these renewable energy over the years, especially in the wake of the worsening global warming. In order to make use of this renewable energy, a power system will have to be set up. Individually, both wind and solar energy are highly unstable. Hence a hybrid of the two systems will tend to even out the energy profile and make it more stable. Since renewable energy is unstable, an energy storage system will have to be installed to ensure that the output power from such a power station can be steadied at a certain level.